OFDM Synchronization Errors and Effects of Phase Noise on WLAN Transceivers. (11th February 2009) - Melliti Melliti, Mourad Mourad; Hasnaoui Hasnaoui, Salem Salem; Bouallegue Bouallegue, Ridha Ridha
Abstract : This work aims at frequency synchronization in OFDM IEEE 802.11g Transceivers. The degradation of performance results from the detrimental effects introduced by frequency offset and phase noise. First, we present a robust method to detect and synchronize the OFDM signal with severe noise and interference corruption based on calculating the accumulated phase difference for each subcarrier. Then, we present a simple architecture to implement the proposed methods. These methods are simulated and analyzed by computer. Finally, we propose many algorithms to correct the common phase error (CPE) of the phase noise and track well its variation.